Increasing Regional Original Tax Revenue (PAD) in the Era of the COVID-19 Pandemic: Strategy of the Pekanbaru City Regional Revenue Agency - Alexsander Yandra; Fildza Idzni Zatuhulwana; Sri Roserdevi Nasution; Dian Rianita; Harsini Harsini (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This study aims to determine the strategy of Local Revenue Agency  (LRA) of Pekanabaru for increasing local tax revenue because there was a decrease in tax revenue in Pekanbaru City during the COVID-19pandemic. For governance funding to run effectively and efficiently and avoid overlapping funding, the government delegated authority to Bapenda Pekanbaru City as an extended branch. Therefore, RRA implemented strategies to increase taxes during the pandemic. This qualitative research uses a qualitative descriptive analysis method that uses data collection methods such as observation, interviews, and documentation. The benchmarks for assessing the success of the strategy, according to Burhan in Zuchri (2016), are through indicators concerning the future of a decision made now, the process that starts with making strategic plans, facilities, and policies in developing implementing plans; certain attitudes and ways of life because strategic plans determine work habits with consideration of the future; as well as linking three strategic plans at the same time, namely strategic plans, medium-term plans, and short-term budgets. Based on the results of research on the strategy of the Pekanbaru City Local Revenue Agency in increasing local original tax revenue (PAD) during the COVID-19pandemic, the strategy of digitizing services and payment methods is the right thing to increase local tax revenues. However, socialization regarding the strategies made has yet to be carried out evenly to the community, as well as the level of public awareness that still needs to be improved in paying taxes